The Tachrift channel-levée turbidite complexes (Tortonian) of the Taza-Guercif basin (South Rifian Corridor, NE Morocco) - Fabrizio Felletti; Mattia Marini; Imad El Kati; Hassan Tabyaoui (Journal of Maps, 2020)
This contribution reports on the field mapping of 9 exceptionally well-exposed channel-levée complexes from Taza–Guercif Basin (NE Morocco), belonging to the Late Miocene Tachrift turbidite system. Separated from each another by hemipelagic marlstones, the mapped channel-levée complexes exhibit thicknesses in the range of 5–25 m. Four main sedimentary facies associations were mapped, including channel-fill sandstones, levée thin-bedded heterolithics, chaotic mass transport deposits, and hemipelagic marlstones. In addition, two end-member styles of channel-fills spatial stacking were recognized, reflecting different modes of channel belt development and/or location along the slope profile, namely: (a) a lateral-migration pattern, resulting from lateral migration of high-sinuosity levéed channel belts, as opposed to (b) a vertically stacked pattern, interpreted to reflect the vertical aggradation of levéed channel belts with a relatively low sinuosity. The geological map accompanying this contribution provides the basis for more in-depth sedimentological investigations on the channels of the Tachrift turbidite system.